A fleeting empire : early Stuart Britain and the merchant adventurers to Canada - Nicholls, Andrew D., 1965- (McGill-Queen's University Press, 2010)
Before the future of North American rule was decided by the battle between British and French forces on the Plains of Abraham, Britain's emerging imperial interests were represented by ambitious merchants and privateers. A Fleeting Empire examines the lives and exploits of early European adventurers in North America, revealing the murky mix of self-interest, patriotism, and adventure that motivated them. The union of the English and Scottish crowns in 1603 gave rise to a new British seafaring community, which the early Stuart monarchy used to pursue some of the first commercial and colonial ventures in North America. Among those who sailed across the Atlantic were the Kirke brothers, who in 1629 forced Samuel de Champlain's surrender of Quebec, Sir William Alexander of Menstrie, a rising political figure and patentee of Nova Scotia, and James Stewart of Killeith, leader of a colony on Cape Breton Island. King Charles I was more concerned with brokering a peace with France than looking to the new world, so the gains of the merchant adventurers were short-lived, but their adventures provide a tantalizing glimpse of a moment of British colonial control, suggesting what might have been. Andrew Nicholls showcases the enterprises of knights and privateers alike, providing a fascinating account of early European colonies, commerce, and military force in North America. A Fleeting Empire forces us to see the early histories of Canada and the United States in a new light.